Teaching Geography on the basis of contemporary conflicts. Studying Ireland through films. (Huellas, 2015)
Conflicts which question citizens’ everyday life in different territories, represent one of the interests of geographical studies, in this particular case, the focus is placed inIrelandfrom the perspective of nationalisms. As teachers and researchers, working towards the enactment of dialogue between the production of knowledge and its application to teaching constitutes our central aim, which tends to promote significant learning.Approaching current geographical conflicts contributes to generating elements of analysis that will help understand the varied and multiple realities which occur in distant territories. Among the teaching objectives of the social sciences, we can find the integral make-up of citizens. Thus, films offer rich opportunities for teaching and learning situations which might promote students’ reflection and critical thinking, necessary tool to interpret different territorial expressions and configurations.
Keywords: Geography – teaching – films – Ireland – conflict.